2017
DOI: 10.1016/j.compositesb.2016.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale experimental investigation of the viscous nature of damage in Advanced Sheet Molding Compound (A-SMC) submitted to high strain rates

Abstract: This paper aims to present an experimental multi-scale analysis of quasi-static and high strain rate damage behavior of a new formulation of SMC composite (Advanced SMC). In order to study its capability to absorb energy through damage accumulation, Randomly Oriented (RO) and High oriented (HO) A-SMC composites damage has been investigated at both microscopic and macroscopic scales. A specific device has been developed in order to perform Interrupted Dynamic Tensile Tests (IDTT) which allows analyzing the evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…To formulate the equation of SMC composites, it is necessary to have enough information about mechanical properties and especially damage phenomena under different modes of loading such as monotonic or fatigue. 10,11 Fatigue response of composites is usually characterized by the Wöhler curve, which is a curve giving the value of cyclic stress/strain amplitude versus the number of cycles to failure, N. 2,[12][13][14][15][16] The parameters that can affect the cyclic behavior are fiber orientations, applied stress/ strain, temperature, frequency, and self-heating. 2,[14][15][16] Strain rate and temperature are two important parameters, which effect on material behavior under different solicitation modes such as tension, compression, shear, and torsion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To formulate the equation of SMC composites, it is necessary to have enough information about mechanical properties and especially damage phenomena under different modes of loading such as monotonic or fatigue. 10,11 Fatigue response of composites is usually characterized by the Wöhler curve, which is a curve giving the value of cyclic stress/strain amplitude versus the number of cycles to failure, N. 2,[12][13][14][15][16] The parameters that can affect the cyclic behavior are fiber orientations, applied stress/ strain, temperature, frequency, and self-heating. 2,[14][15][16] Strain rate and temperature are two important parameters, which effect on material behavior under different solicitation modes such as tension, compression, shear, and torsion.…”
Section: Introductionmentioning
confidence: 99%
“…In SMCs, the bestknown damage mechanisms are matrix cracking, interfacial debonding: the interface between fibers and matrix, pull out or tearing, fiber breakage and delamination between layers for laminated composites. 10,17,[22][23][24] The risk of these damages is that they are sometimes undetectable to the naked eye as their location internal to the structure. Depending on the distribution and the geometry of the components in the matrix, the SMC composite will exhibit anisotropic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, for discontinuous fiber reinforced polymers, a lot T of studies have revealed that the fiber-matrix interface failure can be defined as the predominant local damage mechanism [13][14][15][16][17][18][19][20][21][22]. The experimental analysis has revealed that local damage generally begins by debonding the most misoriented fibers when the local normal stress reaches a critical value.…”
Section: Introductionmentioning
confidence: 99%
“…Then, it progressively propagates to less misoriented fibers by coupling normal and shear interface stresses [15]. Under tension, damage initiation is generally observed for 20% to 30% of the failure stress [14][15][16][17][18][19][20][21][22]. For short fiber reinforced thermoplastic, the ductility of the matrix around the fibers leads to diffuse microcracking.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers studied the mechanical behavior of a glass fiber reinforced composite and presented their connection with the fiber strength and modulus, fiber weight fraction, orientation, type, chemical stability, matrix strength and the interface bonding between the fiber and the matrix [12][13][14][15][16][17][18].…”
mentioning
confidence: 99%